The Reality of Practicing Environmental Citizenship Behaviors "A Study Applied to Beneficiaries from Community Associations Services in Ha’il" - Eldiasty, Ali; Ibrahim, Neveen; Soliman, Manal; ALShammary, Mona H.; Helal , Ibrahim (European Journal of Sustainable Development, 2023)
The study aimed at investigating the reality of environmental citizenship behaviors practice among the beneficiaries from community associations in Ha’il. These behaviors are identified scientifically by national organizations to include environmental personal responsibility, environmental justice and environmental participation. The researchers utilized the sample social survey as an instrument for measuring environmental citizenship behaviors. The research population included 1030 beneficiaries. A random sample of 10%, hundred and three (103) participants, out of the total research population was drawn using the random tables method. Data was collected in the period from (23/5/2022 to 10/11/2022). Findings revealed the highest practiced behaviors as: environmental personal responsibility, environmental justice, and environmental participation with averages of 4.33, 4.23 and 4.08, respectively. Researchers recommended using training programs and providing a local database of individuals’ activities that support environmental citizenship behaviors Key Words: Environmental citizenship behaviors, Environmental personal responsibility, Environmental justice, Environmental participation, Community associations, Ha’il city